A Corrole‐Based Covalent Organic Framework Featuring Desymmetrized Topology. (3rd February 2020) - Zhao, Yanming; Dai, Wenhao; Peng, Yunlei; Niu, Zheng; Sun, Qi; Shan, Chuan; Yang, Hui; Verma, Gaurav; Wojtas, Lukasz; Yuan, Daqiang; Zhang, Zhenjie; Dong, Haifeng; et al.
Abstract: Herein, for the first time, we present the successful synthesis of a novel two‐dimensional corrole‐based covalent organic framework (COF) by reacting the unusual approximately T‐shaped 5, 10, 15‐tris( p ‐aminophenyl)corrole H3 TPAPC with terephthalaldehyde, which adopts desymmetrized hcb topology and consists of a staggered AB stacking structure with elliptical pores. The resultant corrole‐based COF, TPAPC‐COF, exhibits high crystallinity and excellent chemical stability. The combination of extended π‐conjugated backbone and interlayer noncovalent π–π interactions endows TPAPC‐COF with excellent absorption capability in the entire visible‐light and even near‐infrared regions. Moreover, this work suggests the promise of TPAPC‐COF as a new class of photoactive material for efficient singlet‐oxygen generation with potential photodynamic therapy application as demonstrated by in vitro anticancer studies. Abstract : Ein COF für alle Fälle : Ein neuartiges, Corrol‐basiertes, zweidimensionales kovalentes organisches Gerüst (COF) mit desymmetrisierter Topologie wurde hergestellt. Es zeigt eine bemerkenswerte Lichtabsorption im langwelligen sichtbaren und IR‐Bereich, dient als photoaktives Material zur Erzeugung von Singulett‐Sauerstoff und zeigt eine ausgezeichnete antitumorale Wirkung.